Antioxidant properties of Senna siamea and effects on sports performance in Wistar rats - Agbodjogbé, Wilfrid K. D-D.; TITO, Albérick S.I.; Adjakpahoun, Gérard; Messan, Folly; DANSOU, Pierre H. (My University, 2022)
The objective of this study was to evaluate the antioxidant properties of Senna siamea and their effects on sports performance in rats. A total of 15 male Wistar rats were used and divided into 3 groups. The GrpEDSE and GrpED+Entr groups were each subjected to 7 mL/kg of distilled water by body weight, and then the GrpSS+Entr group was treated with 300 mg/kg body weight of aqueous extract of Senna siamea leaves. Rats belonging to GrpED+Entr, GrpSS+Entr groups were subjected to swimming for fifteen days. Twenty-four hours after the last training session, the evaluation was made. The results revealed that the studied plant has an antioxidant property with a value of 353.61±11.10 mmol EAA/mg. Then, the training induced a significant increase (p˂0.01) in swimming performance in treated rats belonging to GrpSS+Entr groups with a running time of 293.452±18.319 min. These extracts of Senna siamea leaves represent natural antioxidants and would thus participate in the improvement of performances in sportsmen. © 2022 International Formulae Group. All rights reserved.
Keywords: KPlants; aqueous extract; swimming; wistar rats.